THE STUDY OF ACCEPTANCE, PERCEPTION AND SATISFACTION IN THE ADOPTION OF RAJAMANGALA SRIVIJAYA TRANG INTERACTIVE AQUARIUM - Ekudompong, Passana; Khanthanurak, Sirirak (Journal of Industrial Education, 2019)
The objectives of this study were to 1) study the acceptance of the users of the interactive aquarium, 2) study the satisfaction of users of the interactive aquarium, and 3) study the effects of an adoption of the interactive aquarium. The sample of this study was 400 users of Rajamangala Srivijaya Trang interactive aquarium which was calculated by using Taro Yamane’s formula with purposive sampling according to the actual number of users. The data was collected from the trial of the interactive aquarium during March – November 2018. The tools used in this study were interactive aquariums, the acceptance of the users of the interactive aquarium questionnaires, the satisfaction of the users of the interactive aquarium questionnaires, the perception of the users of the interactive aquarium questionnaires and the statistics used in the data analysis were frequency, percentage, mean and standard deviation and was performed using independent t-test, one-way ANOVA and Pearson’s product moment correlation. The results revealed that most respondents were female, under 25 years of age. Most respondents were students of Rajamangala University of Technology Srivijaya. The majority of the respondents had a moderate level of fishery knowledge and had a bachelor's degree. It was found that, the acceptance of users of the interactive aquarium were knowledge level persuasion level decision level implementation level and confirmation level, the satisfaction of users of the interactive aquarium was high level and the perception of users of the interactive aquarium was high level. The hypothesis I testing results showed that gender was the factor affecting the perceived adoption of the interactive aquarium while age and status affected the satisfaction of the adoption of the interactive aquarium. The hypothesis II was found that the relationship analysis found that the adoption of interactive aquariums affected satisfaction of users.